2020
DOI: 10.14488/bjopm.2020.018
|View full text |Cite
|
Sign up to set email alerts
|

Reverse logistics performance measures: a survey of Brazilian companies

Abstract: Goal: The purpose of this research was to determine the most frequently used performance measures for the evaluation of reverse logistics in Brazilian companies. Furthermore, we sought to verify whether a correlation exists between certain performance measure dimensions (cost, asset management, customer service, and productivity), company size (micro, small, medium, and large), and their sectors of the economy. Design/Methodology/Approach: A survey of 125 Brazilian companies from different industrial sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Examining the literature review, we found that previous studies in the field of RL have been conducted on several key topics; namely, RL network design (Yan and Yan (2019); Zarbakhshnia et al , 2019; Liao, 2018; John et al , 2018; Alshamsi and Diabat, 2017; Yu and Solvang, 2016; Kilic et al , 2015); Model for the evaluation of RL performance (Hammes et al , 2020; Kazancoglu et al , 2020; Chaves et al , 2020; Han and Trimi, 2018; Peña-Montoya et al , 2020); Investigation of critical success factors in RL implementation (Chakraborty et al , 2018; Adabavazaeh and Nikbakht, 2019; Mangla et al , 2016); Identification of different options in RL and choosing the best option (Wang et al , 2019; Agrawal et al , 2016); RL for sustainability (Asees and Ali, 2019; Agrawal and Singh, 2019); Investigation of the barriers to RL implementation (Sirisawat and Kiatcharoenpol, 2018; Ali et al , 2018; Bouzon et al , 2018; Prakash and Barua, 2016; Bouzon et al , 2016; Bouzon et al , 2016a) and few studies in supply chain management and RL have been conducted using Twitter social media data (Schmidt et al , 2020; Sharma et al , 2020; Tseng et al , 2019; Iftikhar and Khan, 2018; Singh et al , 2018; Mishra et al , 2017; Chan et al , 2016; Chae, 2015; He et al , 2013). We also found that research on the use of customer feedback in RL decisions is very limited (Mishra et al , 2017).…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the literature review, we found that previous studies in the field of RL have been conducted on several key topics; namely, RL network design (Yan and Yan (2019); Zarbakhshnia et al , 2019; Liao, 2018; John et al , 2018; Alshamsi and Diabat, 2017; Yu and Solvang, 2016; Kilic et al , 2015); Model for the evaluation of RL performance (Hammes et al , 2020; Kazancoglu et al , 2020; Chaves et al , 2020; Han and Trimi, 2018; Peña-Montoya et al , 2020); Investigation of critical success factors in RL implementation (Chakraborty et al , 2018; Adabavazaeh and Nikbakht, 2019; Mangla et al , 2016); Identification of different options in RL and choosing the best option (Wang et al , 2019; Agrawal et al , 2016); RL for sustainability (Asees and Ali, 2019; Agrawal and Singh, 2019); Investigation of the barriers to RL implementation (Sirisawat and Kiatcharoenpol, 2018; Ali et al , 2018; Bouzon et al , 2018; Prakash and Barua, 2016; Bouzon et al , 2016; Bouzon et al , 2016a) and few studies in supply chain management and RL have been conducted using Twitter social media data (Schmidt et al , 2020; Sharma et al , 2020; Tseng et al , 2019; Iftikhar and Khan, 2018; Singh et al , 2018; Mishra et al , 2017; Chan et al , 2016; Chae, 2015; He et al , 2013). We also found that research on the use of customer feedback in RL decisions is very limited (Mishra et al , 2017).…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…These activities in a food supply chain in terms of CO 2 (carbon dioxide), NO x (nitrogen oxide), SO 2 (sulfur dioxide) and PM (particulate matter) emissions have been predicted through a system dynamics model for the years 2020 to 2024. Chaves et al (2020) have determined the most frequently used performance measures for the evaluation of RL in Brazilian companies. Furthermore, they sought to verify whether a correlation exists between certain performance measure dimensions (cost, asset management, customer service and productivity), company size (micro, small, medium and large) and their sectors of the economy.…”
Section: Reverse Logisticsmentioning
confidence: 99%
“…According to Chaves et al (2020) it is also called the Coordinating System, the first and most important key element of the RL process since it is responsible for this system's overall management and performance. It is the planning stage that takes place throughout the whole RL process.…”
Section: Integrationmentioning
confidence: 99%
“…It is the refined selection (filtering) of waste and accurate definition of quantities to be collected and transported to processing facilities. Also called Grading, it starts when materials to be collected must be screened for entering the return stream according to their functionality and determining the flow to be followed in the RL process (Chaves et al, 2020). According to Agrawal et al (2015) this stage represents the main entrance of RL and constitutes a set of practices performed usually by retailers to identify the products which are allowed into the RL system or given back to the user after resolving issues at their end or to proper disposal (Agrawal et al, 2016a).…”
Section: Gatekeepingmentioning
confidence: 99%
See 1 more Smart Citation